Human Ecology: Saving the Nation as a Strategy for Successful Development - V. N. Kolesnikov; N. D. Shandybina; S. S. Erium (Управленческое консультирование)
The article describes an issue of an affordable and comfortable spinal column diagnostics as well as the treatment of a wide spectrum of spine and posture distortions of the Russian population from the standpoint of human ecology. Important aspects of the implementation of the state health development strategy are discussed from the perspective of Russian specialists in the field of modern diagnostic medical equipment that include proposals for import substitution in Russia. The article uses descriptive-evaluative and comparative research methods to analyse the current situation in the field of evidence-based diagnostic medicine.